Implementation of Special Protection Policy in Child-Friendly City Program in Banda Aceh City, Aceh Province - Nurul Wariyin Erzak; M. Irwan Tahir; Imelda Hutasoit (Sean Institute, 2025)
The Child-Friendly City (KLA) Program in Banda Aceh City has faced various challenges, including child exploitation, violence, low access to education, limited facilities for children with disabilities, and obstacles to coordination between institutions. This study aims to analyze the implementation of special protection policies in the KLA Program in Banda Aceh City, identify supporting and inhibiting factors, and formulate strategies to overcome these obstacles. This study uses a qualitative method with an inductive approach. Data were collected through interviews, observations, and documentation, then analyzed using NVivo software for data exploration, coding, and interpretation. The implementation of special protection policies has gone quite well, but has not been optimal in reducing cases of violence and exploitation of children. Partnership support, clear regulations, and the level of public trust are supporting factors. On the other hand, obstacles such as sectoral egos, limited facilities and infrastructure, and low public awareness are still the main obstacles. The recommended strategies include optimizing the program, increasing coordination between parties, and educating the public about child protection.